Effects of ethical behavior on employee performance mediated by job commitment among service sector employees of Malaysia - Osman-Gani, Aahad M.; Anwar, Md. Aftab; Rahman, Muhammad Sabbir (2016)
In today’s competitive business environment, most organizations are trying to excel by outsmarting others through all means resulting in many cases of violations in ethical standards and moral values by organizational leaders. The recent episodes of such corporate scandals and ethical violations give testimony to this effect. There is an urgent need to include more ethics related courses and training programs in universities and in corporate programs. Although some research has been done on the effects of work ethics and organizational commitment in the western hemisphere, no empirical study was found to have conducted in the dynamic Asia-Pacific region, particularly in the service industry. This research attempted to bridge the research gap by identifying the nature of relationship existing between ethical behavior and employee performance as well as by identifying the mediation effects of commitment to job. The study was conducted on employees working in services sector companies operating in Malaysia. A field survey was conducted on a sample of 263 employees who were selected randomly from Malaysian service industry. Structural equation modeling technique was used for conducting data analysis in order to test the research hypotheses. The findings of this empirical investigation revealed that there is significant positive relationship between ethical behavior and performance at work. The results also supports that commitment to job mediates the relationship between ethical behavior and employee performance. Based on the findings of this study, implications for professional practice and for future research are presented that are relevant to the fields of organizational management and HRD.